Properties of starch based active packaging - Nooratikah Mohamad.
Polymer and polymer-based composite materials with electro-conductive properties are material with several potential applications. New materials are being offered in every area and novel products are constantly being introduced. Polyaniline (PANI) was chemically synthesized by oxidizing aniline with ammonium persulfate (APS) with and without hydrochloric acid (HCl). The resulted polyaniline was in a powder form which was characterized by electrical conductivity. PANI and PANI-HCl films were developed from the polyaniline powder using different concentration. The mechanical analysis of PANI and PANI-HCl films which tensile strength (TS), Young‟s Modulus of elasticity (YM) and elongation at break (EAB) were investigated. PANI films exhibits excellent mechanical properties which give the tensile strength and elongation at break, however, the Young‟s modulus increased with higher loading of PANI. This is suggesting a lack of interfacial adhesion between the PANI particles and the starch matrix. The sorption isotherm model which is Peleg Model fittings showed agreement to the experimental data and predicted data for the investigation of water absorption and equilibrium moisture content of starch based film. Moreover, equilibrium moisture content plays an important role in starch based plastic manufacturing especially storage and transportation to prevent deterioration of film which can reduce its shelf life. The moisture sorption characteristic of starch based film is critical to determine their stability and application in active packaging field.